Faith-Inspired Health Care Provision in Ghana : Market Share, Reach to the Poor, and Performance - Olivier, Jill; Shojo, Mari; Wodon, Quentin (Taylor and Francis, 2014)
It is commonly accepted that faith-inspired institutions (FIIs) provide a substantial share of health services in sub-Saharan Africa. To substantiate this perception, one would ideally like to have a comprehensive assessment of the scope and scale of all health-related services provided not only by government facilities and faith-inspired providers, but also by private-for-profit providers and other non-religious non-governmental organizations (NGOs) and community-based organizations and initiatives—including categorization according to primary areas of response such as HIV/AIDs. Such comprehensive overviews are unfortunately not currently available. It is nevertheless possible to take one (partial) step towards such comprehensive assessments in specific countries by comparing and interpreting the market share estimates for the health care services provided by various types of providers obtained with both facilities and household survey data, and to measure the facilities’ “reach to the poor” (understood here as a comparative market share assessment of various types of providers among segments of the population according to their level of well-being, and especially among the poor). In addition, qualitative work can help reveal the reasons why patients tend to choose one type of provider versus another. The objective of this article is to do precisely this in the case of Ghana.